Regulation of Vascular Endothelial Cell Polarization and Migration by Hsp70/Hsp90-Organizing Protein - Li, Jingyu; Sun, Xiaodong; Wang, Zaizhu; Chen, Li; Li, Dengwen; Zhou, Jun; Liu, Min (PLOS ONE, 2012)
Hsp70/Hsp90-organizing protein (HOP) is a member of the co-chaperone family, which directly binds to chaperones to regulate their activities. The participation of HOP in cell motility and endothelial cell functions remains largely unknown. In this study, we demonstrate that HOP is critically involved in endothelial cell migration and angiogenesis. Tube formation and capillary sprouting experiments reveal that depletion of HOP expression significantly inhibits vessel formation from endothelial cells. Wound healing and transwell migration assays show that HOP is important for endothelial cell migration. By examination of centrosome reorientation and membrane ruffle dynamics, we find that HOP plays a crucial role in the establishment of cell polarity in response to migratory stimulus. Furthermore, our data show that HOP interacts with tubulin and colocalizes with microtubules in endothelial cells. These findings indicate HOP as a novel regulator of angiogenesis that functions through promoting vascular endothelial cell polarization and migration.